2021
DOI: 10.14814/phy2.14862
|View full text |Cite
|
Sign up to set email alerts
|

Functional lymphatic reserve capacity is depressed in patients with a Fontan circulation

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…4,14 The evidence describing functional changes in the lymphatic system in Fontan patients remains scarce. 16,27 Mohanakumar et al reported 17% lower occlusion pressure of the lower extremity collecting lymphatic vessels compared to age, gender, and weight-matched controls but was unable to confirm findings in a larger population. 16,27 In a rare study connecting lymphatic complications with morphological findings, Dori et al showed increased TD diameters in patients with PLE and PB compared to Fontan patients without complications.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4,14 The evidence describing functional changes in the lymphatic system in Fontan patients remains scarce. 16,27 Mohanakumar et al reported 17% lower occlusion pressure of the lower extremity collecting lymphatic vessels compared to age, gender, and weight-matched controls but was unable to confirm findings in a larger population. 16,27 In a rare study connecting lymphatic complications with morphological findings, Dori et al showed increased TD diameters in patients with PLE and PB compared to Fontan patients without complications.…”
Section: Discussionmentioning
confidence: 92%
“…16,27 Mohanakumar et al reported 17% lower occlusion pressure of the lower extremity collecting lymphatic vessels compared to age, gender, and weight-matched controls but was unable to confirm findings in a larger population. 16,27 In a rare study connecting lymphatic complications with morphological findings, Dori et al showed increased TD diameters in patients with PLE and PB compared to Fontan patients without complications. 19 While not proving causality, the findings of an inverse correlation between TD diameter and the ability of the TD to contract and increase pressure during manual occlusion goes some way in increasing knowledge of the challenges of Fontan individuals with lymphatic failure.…”
Section: Discussionmentioning
confidence: 92%
“…Hyperthermia leads to the increased interstitial fluid formation and has been used to evaluate lymphatic function. Kelly et al (2019) and Mohanakumar et al (2021) used NIRF imaging to investigate the effects of hyperthermia on the peripheral lymphatic vessels. Furthermore, Olszewski et al (1977) investigated the effects of hyperthermia using lymphatic cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…Like in the primary study as well as several others, especially in patients with lymphatic complications, we observed a higher lymphatic propulsion velocity in the ipsilateral arm compared contralaterally ( P = 0.01). 15 , 28 , 29 This may be caused by the lymphatic vessels being slightly more contracted and with reduced compliance due to collagen deposition, so that if the lymphatic vessel diameter decreases, the velocity of the fluid increases during a constant flow.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,18 In line with above-mentioned theories, it was highly interesting that BCRL patients and patients with lymphatic morphological abnormalities were not able to increase CF significantly (Table 1), whereas their own contralateral arms as well as remaining subgroups demonstrated expected increases in CF. Mohanakumar et al 28 found that Fontan patients, a particular group of patients with congenital heart disease prone to lymphatic complications, have similar difficulties in increasing CF after inducing hyperthermia.…”
Section: Decreased Ability To Mobilize Reserve Capacity Of Lymphatic ...mentioning
confidence: 99%